Optimalisasi Perawatan Fresh Water Generator guna Mempertahankan Produksi Air Tawar di Kapal Pgn Fsru Lampung: Optimalisasi Perawatan Fresh Water Generator guna Mempertahankan Produksi Air Tawar di Kapal Pgn Fsru Lampung - S. Wulandari, Rr. Retno; Prayogo, Darul; Suhartini; Fariz Fauzy, M. (Politeknik Penerbangan Makassar, 2019)
FWG (freshwater generator) can produce fresh water that can be used for drinking water, cooking, washing and even using for other important machines which use fresh water as a cooling medium. FWG fresh water is produced using the evaporation method. So, this fresh water is produced by evaporation of sea air using heat from one heat source. So, in order to produce clean water at 70 degrees we need to reduce atmospheric pressure, which is done by creating a vacuum in the space where evaporation takes place. Also, as a result of packaging from seawater evaporating at lower temperatures, the water will be cooled and collected then transferred to a tank. At this time most ships use the method, reverse osmosis which is one of the methods used on the deck to produce fresh water.